Potensi Ekstrak Metanol Kulit Batang Lannea coromandelica (Houtt.) Merr. Terhadap Staphylococcus aureus Dan Analisis Metabolit Sekunder Utamanyanya - Syamsurya, Syamsurya; Ahmad, Ahyar; Firdaus, Firdaus (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2016)
This study aims to determine the potential of the methanol extract of the stem bark Lannea coromandelica (Houtt.) Merr. against Staphylococcus aureus and to analyze the main secondary metabolites. Staphylococcus aureus antibacterial activity test was performed by Mueller-Hinton agar medium whereas the secondary metabolite analysis of the methanol extract of the stem bark is conducted by GC-MS instrument. Results of research the methanol extract of bark Lannea coromandelica (Houtt.) Merr showed antibacterial activity against Staphylococcus aureus with inhibition zone diameter each at a concentration of 2.5% by 7.3 mm by 8.6 mm 5% and 10% of 10.4 mm. Selanjunya result of analysis by using GC-MS showed the presence of compounds 5-hidroksimetilfurfural and compounds 1, 2, 3-benzenetriol potential as an antibacterial Staphylococcus aureus. Furthermore, the results of analysis by GC-MS instrumeny showed the presence of compounds 5-hidroksimetilfurfural and compounds 1, 2, 3-benzenetriol potential as an antibacterial Staphylococcus aureus.